The elements of Cantor sets : with applications - Vallin, Robert W. (Hoboken, New Jersey : Wiley, 2013)
"This book is a thorough introduction to the Cantor (Ternary) Set and its applications and brings together many of the topics (advanced calculus, probability, topology, and algebra) that mathematics students are required to study, but unfortunately are treated as separate ideas. This book successfully bridges the gap between how several mathematical fields interact using Cantor Sets as the common theme. While the book is mathematically self-contained, readers should be comfortable with mathematical formalism and have some experience in reading and writing mathematical proofs. Chapter coverage includes: a biography of Cantor; an introduction to the Cantor (Ternary) Set; Self-Similar Sets and Fractal Dimensions; sums of Cantor Sets; the role of Cantor Sets to create pathological functions; and additional topics such as continued fractions, Ana Sets, and p-adic numbers"--
10.4 Differences of Cantor Sets10.5 Products of Cantor Sets; 10.6 Cantor Target; 10.7 Ana Sets; 10.8 Average Distance; 10.9 Non-Averaging Sets; 10.10 Cantor Series and Cantor Sets; 10.11 Liouville Numbers and Irrationality Exponents; 10.12 Sets of Sums of Convergent Alternating Series; 10.13 The Monty Hall Problem; 11 Epilogue; References; Index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Cantor, George, -- 1941-; Cantor, George, -- 1941-; Cantor sets; Measure theory; Mathematical analysis; MATHEMATICS / Mathematical Analysis; Cantor, George, 1941-; Cantor sets; Mathematical analysis; Measure theory; Electronic books; Electronic books